Extracts of Sida cordifolia contain polysaccharides possessing immunomodulatory activity and rosmarinic acid compounds with antibacterial activity - Haroon Iqbal; Claire L. Wright; Sue Jones; Goncalo Rosas da Silva; John McKillen; Brendan F. Gilmore; Owen Kavanagh; Brian D. Green (BMC, 2022)
Abstract Background The overuse of antibiotics has led to increased antimicrobial resistance, but plant-derived biological response modifiers represent a potential alternative to these drugs. This investigation examined the immunomodulatory and antibacterial activities of Sida cordifolia (used in ethnomedicinal systems to treat infectious disease). Methods Successive extractions were performed from the roots of these plants in hexane, chloroform, methanol and water. Immunomodulatory activity was determined in a series of experiments measuring the responses of splenocytes, macrophages and an in vivo model of innate immunity (Galleria mellonella). Antibacterial activity was assessed by determining minimum inhibitory/bactericidal concentrations (MIC/MBCs) for various Gram-positive and Gram-negative bacterial strains. Results Immunomodulatory activity was confined to the aqueous extract, and further fractionation and biochemical analysis yielded a highly potent polysaccharide-enriched fraction (SCAF5). SCAF5 is a complex mixture of different polysaccharides with multiple immunomodulatory effects including immune cell proliferation, antibody secretion, phagocytosis, nitric oxide production, and increased expression of pro-inflammatory cytokines. Furthermore, Galleria mellonella pre-treated with SCAF5 produced more haemocytes and were more resistant (P < 0.001) to infection with methicillin-resistant Staphylococcus aureus (MRSA) with a 98% reduction in bacterial load in pre-treated larvae compared to the negative control. The antibacterial activity of Sida cordifolia was confined to the methanolic fraction. Extensive fractionation identified two compounds, rosmarinic acid and its 4-O-β-d-glucoside derivative, which had potent activity against Gram-positive antibiotic-resistant bacteria, including MRSA. Conclusions Sida cordifolia counters bacterial infections through a dual mechanism, and immunomodulatory polysaccharides from this plant should be isolated and characterised to realise their potential as anti-infective agents. Such properties could be developed as an antibiotic alternative (1) in the clinic and (2) alternative growth promoter for the agri-food industry.